Urgensi Pembentukan Undang-Undang yang Mewadahi Lembaga Independen sebagai Perwujudan Green Election dalam Green Constitution - Ismawati Septiningsih; Itok Dwi Kurniawan (Fakultas Hukum Universitas Islam Indonesia, 2024)
Elections are a method of direct voting to elect leaders at the executive and legislative levels. This election concept is commonly found in countries with democratic government systems. There are various problems in this system. These problems include the accuracy of voter data, problems in logistics, and low community participation. There are various factors that underlie this problem. The election procedure in Indonesia which is still conventional is suspected to be one of the causes. In the last general election, which was held simultaneously, it resulted in many casualties. The problems that occurred in the use of the conventional method itself became a problem from the beginning of the formation of the KPU. Technological developments require people to be able to adapt quickly and the impact of the Covid-19 pandemic that attacks almost all over the world has clouded the atmosphere. As a result, people have to limit their activities at homeTherefore, we need a new method and procedure in organizing this democratic party. Green Election is an election method using technology as the basis. This concept is considered efficient because it reduces paper usage and is considered energy friendly. This is in line with Indonesia's commitment to protecting the environment. And in line with the SDGs concept agreed upon by various countries. However, the application of this concept also requires maturity related to existing infrastructure and technology. So that the application of this technology can be used optimally by the entire community